Symptomatic Gallstones in the Young: Changing Trends of the Gallstone Disease-Related Hospitalization in the State of New York: 1996 - 2010 - Chilimuri, Sridhar (J Clin Med Res, 2017)
BACKGROUND: The aim of the study was to evaluate if the gallstone-related hospitalizations in the young (< 20 years of age) have increased over time in both the Bronx County and New York State as a whole. METHODS: We retrospectively reviewed 15 years (1996 - 2010) of Statewide Planning and Research Cooperative System (SPARCS) data of New York State Department of Health. Patients with ICD-9 code diagnosis of 574 (cholelithiasis) among the first three discharge diagnoses were reviewed. RESULTS: Total number of all cause admissions to hospitals had increased from 2.44 million to 2.77 million (1996 - 2010). However, gallstone-related hospitalizations had decreased from 1.7% to 1.2%. It was noted that there was a 30% increment in the proportion of those below 20 years of age with gallstone disease requiring hospitalization over the same period. This young patient population contributed only 2.04% to all gallstone-related hospitalizations in 1996, whereas it had increased to 2.96% in 2010. This trend was more pronounced in women, Hispanics and in those who were residing in the Bronx County as compared to all other New York counties combined. CONCLUSION: The gallstone-related hospitalizations in the young (< 20 years of age) have increased over time in both the Bronx County and New York State as a whole. This could be due to increasing prevalence of risk factors such as obesity, physical inactivity, diabetes and early pregnancy.